Mechatronics engineering and electrical engineering proceedings of the 2014 International Conference on Mechatronics Engineering and Electrical Engineering (CMEEE 2014), Sanya, Hainan, P.R. China, 17-19 October 2014 - Sheng, Ai (CRC Press/Balkema, 2015)
The 2014 International Conference on Mechatronics Engineering and Electrical Engineering (CMEEE2014) was held October 18-19, 2014 in Sanya, Hainan, China. CMEEE2014 provided a valuable opportunity for researchers, scholars and scientists to exchange their new ideas and application experiences face to face together, to establish business or research relations and to find global partners for future collaboration. The papers in this book are selected from more than 500 papers submitted to the 2014 International Conference on Mechatronics Engineering and Electrical Engineering (CMEEE2014)